Lecturer Based Supportive Tool Development and Approaches for Learning Material Sharing under Bandwidth Limitation - Kautsar, Irwan Alnarus; Kubota, Shinichiro; Musashi, Yasuo; Sugitani, Kenichi (Journal of Information Processing, 2016)
総合学術電子ジャーナルサイト「J-STAGE」－国内で発行された学術論文全文を読むことのできる、日本最大級の総合電子ジャーナルプラットフォームです。
Keywords: __C:filed:1